EPIDEMIOLOGICAL SITUATION OF DERMATOMYCOSES IN AZERBAIJAN FOR 2017–2019 ACCORDING TO THE NEW CLASSIFICATION - Akhmedova, S.J. (World of Medicine and Biology, 2023)
During the period 2017–2019, 128 episodes of referral to skin and venereological institutions in Baku and 1358 episodes in the Republic of Azerbaijan were recorded. The classification of dermatomycoses is unstable due to the constant revision of certain provisions in mycology. Of the 128 episodes of superficial skin mycoses based on the traditional form No. 9, mycosis of the scalp is in the first place – 23.8±1.19 %, mycosis of smooth skin – 20.9±1.16 %. multicolored lichen – 15.8±1.12 %. Thus, microscopic diagnostics makes it possible to detect the mycelium, and not the specific identity of the mycotic agent. This is the main imperfection of the classification based on the reporting form No. 9. A modified classification of superficial mycoses of the skin is proposed, combining two approaches. The greatest incidence of mycosis of the scalp was 475 episodes (35.2±1.1 %), mycosis of smooth skin – 390 episodes (26.8±1.1 %), multicolored lichen – 291 episodes (21.6 %±0.8). Thus, the modified clinical structure of superficial skin mycoses, taking into account the tissue and topographic localization of the mycotic process, makes it possible to significantly simplify the clinical diagnosis of superficial skin mycoses and facilitates the work of dermatologists.
Keywords: dermatophytes; saprophytes; lichen; classification